2010
DOI: 10.3109/1061186x.2010.525652
|View full text |Cite
|
Sign up to set email alerts
|

Using polymeric precipitation inhibitors to improve the absorption of poorly water-soluble drugs: A mechanistic basis for utility

Abstract: The inclusion of certain polymers within solid dispersion or lipid-based formulations can maintain drug supersaturation after dispersion and/or digestion of the vehicle, leading to improvements in bioavailability and variability in exposure. This review presents an overview of the fundamental principles that underpin drug precipitation mechanisms, describes the mechanisms by which precipitation may be inhibited, discusses the methods that can be used to identify polymeric precipitation inhibitors (PPIs), and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
302
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(312 citation statements)
references
References 107 publications
3
302
0
6
Order By: Relevance
“…5,6 In order to maximise the potential of cocrystals, it is critical to include inhibitors in a formulation to prevent or delay the precipitation of the parent drug during dissolution. [7][8][9][10][11][12][13] Although polymeric crystallization inhibitors have been extensively studied in many other systems, in particular amorphous solid dispersions, 14,15 such studies are still rare for cocrystal based formulations. In a recent study, we have found that the competition of intermolecular hydrogen bonding among drug/coformer, drug/polymer, and coformer/polymer was a key factor responsible for maintaining the supersaturation through nucleation inhibition and crystal growth modification in a supersaturated cocrystal solution with a pre-dissolved polymer.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In order to maximise the potential of cocrystals, it is critical to include inhibitors in a formulation to prevent or delay the precipitation of the parent drug during dissolution. [7][8][9][10][11][12][13] Although polymeric crystallization inhibitors have been extensively studied in many other systems, in particular amorphous solid dispersions, 14,15 such studies are still rare for cocrystal based formulations. In a recent study, we have found that the competition of intermolecular hydrogen bonding among drug/coformer, drug/polymer, and coformer/polymer was a key factor responsible for maintaining the supersaturation through nucleation inhibition and crystal growth modification in a supersaturated cocrystal solution with a pre-dissolved polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Three chemi ca l l y di vers e pol ymers i ncl udi ng hydroxypropyl emthyl cel l ul os e a ceta te s ucci na te (HPMCAS), pol yvi nyl pyrrol i done (PVP) a nd pol yethyl ene gl ycol (PEG) were s elected i n the s tudy beca us e they ha ve been wi del y us ed a s preci pitation i nhi bi tors i n other s upers a tura ti ng drug del i very s ys tems a nd a pproved orally commercial products [12][13][14]22 . In order to eva l uate the effectiveness of these pol ymers on i nhi bi ti ng the pha se tra nsformation of cocrys tals, the s tudy was ca rri ed out wi th pol ymers i n both pre -di s s ol ved s ol uti on a nd ta bl et ba s ed formul ations.…”
Section: Introductionmentioning
confidence: 99%
“…Thi s coul d be a chi eved through i ncl us i on of pha rma ceuti ca l exci pi ents a s preci pi ta ti on ( or crys ta l lisation) inhibi tors i n the formul a ti on. A l a rge number of exci pi ents ha ve been expl ored a s preci pi ta ti on i nhi bi tors to ma i ntain drugs i n other s upersaturating drug delivery s ystems s uch a s s olid di s pers i ons a nd l i pi d -ba s ed formul a ti ons [12][13][14] . Thes e exci pients i ncluding polymers, s urfa cta nts a nd cycl odextri ns ca n i nterfere wi th drug nucl ea ti on a nd/or crys ta l growth to i nhi bi t a nd/or retard the drug precipitation from sol uti on.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, CEL release from the commercially available formulation (Celebrex ® ) was much slower in the medium and was equivalent to the maximum solubility of CEL in 0.1N HCl (3 mg/L). PVOH has already been reported as a precipitation inhibitor, able to stabilize supersaturation of drugs (caffeine (Gift et al, 2008), danazol (Warren et al, 2010), estradiol (Megrab et al, 1995) and tacrolimus (Overhoff et al, 2008)) via drug/polymer interactions. In addition to the lower extrusion temperature of this formulation during HME, this could be an important feature to improve the bioavailability of solubility-limited drugs (BSC class II).…”
Section: Plasticized Partially Hydrolyzed Pvohmentioning
confidence: 99%